The Methodological Consistency of Master’s of Education Dissertations at Eduardo Mondlane University (2013 - 2018) - Zimbico, Octavio; Manuel, Arsenia (International Journal of African Higher Education, 2021)
This study examined the methodological consistency of Master of Education dissertations defended at Eduardo Mondlane University (EMU) from 2013 to 2018 using the typology of educational research proposed by Postlethwaite (2005), Norman et al. (2002), and Creswell (2012). The qualitative, comparative study employed a grounded theory design. Data were gathered from a purposive sample of 33 dissertations, available on the university’s Open Institutional Repository. Coding and anonymous analysis were performed of the dissertations’ title, research methodology, and findings. The findings reveal that a large number of these dissertations are not methodologically consistent and thus do not lay the foundation for further research and other interventions for school improvement. They thus point to the need to improve the quality of supervision and research in postgraduate studies in Education at EMU. Key words: EMU, Master’s dissertations, educational research, methodological consistency, supervision